Molecular Biotechnology 2021
DOI: 10.5772/intechopen.89918
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolase-Catalyzed Promiscuous Reactions and Applications in Organic Synthesis

Abstract: The potential of biocatalysis becomes increasingly recognized as an efficient and green tool for modern organic synthesis. Biocatalytic promiscuity, a new frontier extended the use of enzymes in organic synthesis, has attracted much attention and expanded rapidly in the past decade. It focuses on the enzyme catalytic activities with unnatural substrates and alternative chemical transformations. Exploiting enzyme catalytic unconventional reactions might lead to improvements in existing catalysts and provide nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“… 20 However, after 2 years, they reached a single product using cis- and trans -nitroolefin isomers and concluded that the path of this reaction does not go through concerted cycloaddition. 52 Based on the mechanisms related to lipase 53 , 54 and according to the step mechanism of Deng and Mani, the proposed mechanism was presented ( Scheme 2 ). First, imine intermediate 7 forms from the reaction of phenyl hydrazine 2 with aldehyde 1 and then Asp-His dyad 13 activates nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“… 20 However, after 2 years, they reached a single product using cis- and trans -nitroolefin isomers and concluded that the path of this reaction does not go through concerted cycloaddition. 52 Based on the mechanisms related to lipase 53 , 54 and according to the step mechanism of Deng and Mani, the proposed mechanism was presented ( Scheme 2 ). First, imine intermediate 7 forms from the reaction of phenyl hydrazine 2 with aldehyde 1 and then Asp-His dyad 13 activates nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…Short-chain esters are common products in the food and flavor industry . Esterification using an enzyme as a catalyst has advantages over typical acid catalysts because they are efficient under mild conditions . Lipases are widely used in a variety of industries because no cofactor is required; they are stable in organic solvents and can maintain their activity for multiple reuses .…”
Section: Resultsmentioning
confidence: 99%
“…52 Esterification using an enzyme as a catalyst has advantages over typical acid catalysts because they are efficient under mild conditions. 53 Lipases are widely used in a variety of industries because no cofactor is required; they are stable in organic solvents and can maintain their activity for multiple reuses. 54 Moreover, they are suitable for use as effective catalyst for the synthesis of short and medium esters as flavor and aroma constituents in the food industry.…”
Section: Resultsmentioning
confidence: 99%
“…Proteases are used in a broad range of applications, including biorefineries targeting a broad range of biomasses [ 22 ]. However, the known and new proteases positively impact additional processes, such as cascade reactions where proteases have a pivotal role [ 25 ]. Here, we targeted a cascade reaction involving peptide bond cleavage and ester bond formation and demonstrated that the newly designed EH 1AB1C PluriZyme was capable of converting the dipeptide L-carnosine (β-alanine-L-histidine) into L-histidine methyl ester, an intermediate for the design of Schiff base ligands [ 26 ].…”
Section: Introductionmentioning
confidence: 99%